“HIIT” the ExerCube: Comparing the Effectiveness of Functional High-Intensity Interval Training in Conventional vs. Exergame-Based Training - Martin-Niedecken, Anna Lisa; Mahrer, Andrea; Rogers, Katja; de Bruin, Eling D.; Schättin, Alexandra (Frontiers in Computer Science, 2020)
Regular physical activity is crucial for a physically and mentally healthy lifestyle. Training methods such as high-intensity interval training (HIIT) have become increasingly popular as they enable substantial training effects in little time. HIIT typically involves recurring short phases of close-to-maximal exercise intensity, interspersed with low-intensity recovery phases. Originally mainly practiced via uniformly repetitive movements, newer variations include varied functional and holistic exercises (fHIIT). While HIIT facilitates many health advantages, fHIIT is considered more beneficial since it activates more muscles, requires more coordination, strength and balance, and mimics more natural movements which transfer well to daily life. However, fHIIT is a very intense training approach; it requires strong focus and intrinsic motivation to frequently push beyond perceived physical and mental limits. This is a common barrier to exploiting the full potential of this efficient training method. Exergames may facilitate this kind of training due to their playful, immersive, motivating nature. Yet so far, few studies have investigated HIIT-exergames – no fHIIT-exergames. This is possibly because few exergames featured both (1) an effective training concept that is comparable to HIIT, and (2) an attractive and motivating game design. We believe that this lack of holistic integration of both aspects is partly why there is currently little evidence for long-term motivation and training effects in exergame-based training. Our work addresses this gap through the design of an adaptive fHIIT protocol for the ExerCube fitness game system, creating a HIIT-level functional exergame. We conducted a within-subjects study to compare objective and subjective training intensity induced by the ExerCube against a conventional fHIIT session with healthy young adults. Furthermore, we evaluated participants' subjective experience with regards to motivation, flow, and enjoyment during both conditions. Our results contribute empirical evidence that exergames can induce HIIT-level intensity. While perceived physical exertion was slightly lower in the ExerCube condition, it yielded significantly better results for flow, enjoyment, and motivation. Moreover, the ExerCube seemed to enable a dual-domain training (higher cognitive load). We discuss these results in the context of exergame design for fHIIT, and provide practical suggestions covering topics such as safety precautions and physical-cognitive load balancing.